Inflexible stoichiometry in bulk pyrite FeS2 as viewed by in situ and high‐resolution X‐ray diffraction. Issue 5 (28th August 2018) - McAuliffe, Rebecca D.; Shoemaker, Daniel P.
Abstract : The stoichiometry of iron pyrite, FeS2, is rigorously studied using high‐resolution and in situ X‐ray diffraction. The upper bound on the concentration of sulfur vacancies in FeS2 is investigated. Abstract : Non‐stoichiometry is considered to be one of the main problems limiting iron pyrite, FeS2, as a photovoltaic absorber material. Although some historical diffraction experiments have implied a large solubility range of FeS2−δ with δ up to 0.25, the current consensus based on calculated formation energies of intrinsic defects has lent support to line‐compound behavior. Here it is shown that pyrite stoichiometry is relatively inflexible in both reductive conditions and in autogenous sulfur partial pressure, which produces samples with precise stoichiometry of FeS2 even at different Fe/S ratios. By properly standardizing in situ gas‐flow X‐ray diffraction measurements, no significant changes in the lattice parameter of FeS2 can be resolved, which portrays iron pyrite as prone to forming sulfur‐deficient compounds, but not intrinsic defects in the manner of NiS2−δ .